2016
DOI: 10.13189/ujme.2016.040204
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network Model for Estimation of Wear and Temperature in Pin-disc Contact

Abstract: This work aims to investigate experimentally the parameters affecting on the wear debris and the temperature rise due to friction as well as developing the artificial neural network model (ANN) using MATLAB program for predicting the wear, and temperature of disc and pad. Two types of disc made from aluminum and steel are slipping against pad and carried out under dry conditions at different time, rotational speed, and load to examine the wear. The results show that the wear and temperature are increased with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…It was observed that the selected neural network prediction of the wear rate and coefficient of friction were in agreement with the measured values. This was confirmed by the values of MAE and RMSE reasonably low; R and NSE reasonably high as reported by [14,6].…”
Section: Multiple Linear Regression (Mlr)supporting
confidence: 90%
See 2 more Smart Citations
“…It was observed that the selected neural network prediction of the wear rate and coefficient of friction were in agreement with the measured values. This was confirmed by the values of MAE and RMSE reasonably low; R and NSE reasonably high as reported by [14,6].…”
Section: Multiple Linear Regression (Mlr)supporting
confidence: 90%
“…Artificial Neural Networks (ANNs) are revolutionary computing paradigms that try to mimic the biological brain. These ANNs are modeling techniques that are especially useful to address problems where solutions are not clearly formulated or where the relationships between inputs and outputs are not sufficiently known [6,1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of this technology is that ANN models can be trained based on experimental data to recognize solutions. The ANN prediction method has been used in several applications [5][6][7][8][9][10][11][12][13][14][15], such as wear [5][6][7][8][9][10][11][12] and friction [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…An experimental plan was performed on a pin-on-disc machine for obtained experimental results under unlubricated conditions. Hassan et al in [10] gave investigated experimentally the parameters affecting on the wear debris and the temperature rise due to friction as well as developing the model ANN using MATLAB program for predicting the wear, and temperature of disc and pad. Since the hybrid materials had not been enough researched, Sathyabalan et al in [11] have presented application of ANN on the MMC (hybrid LM6 aluminium) which is reinforced by SiC and flyash.…”
Section: Introductionmentioning
confidence: 99%